The Use of Basic Sewing Book to Improve Sewing Ability with Student with Autism - Nurisma Nuraina; Lusie Fajarianie (Universitas Pendidikan Indonesia (UPI), 2021)
The purpose of this study was to determine the use of basic sewing books to improve the ability to sew basting stitches for students with autisms. The method used in this classroom action research is a demonstration learning method. The subjects of this study were 3 students with autisms at Sekolah Luar Biasa Negeri Sukanagara. The use of basic sewing books showed an increase in the ability to sew on a bast stitch in all students. In the third cycle, each student gets a score that exceeds the minimum completeness criteria that have been set, which is 81. This happened because the basic sewing books used were easy to understand and follow by students. This study demonstrates that the use of an easy-to-understand basic sewing book will accelerate students' understanding. In addition, a good basic sewing book will also make it easier for teachers to guide students, especially for students with autisms.